Development Of An Improved Method To Measure In Situ Thermal Rock Properties In A Single Drill Hole - G. Danko; M. McPherson (Society for Mining, Metallurgy & Exploration, 1987)
Methods of measuring in situ rock thermo-physical properties are rapidly evolving. Among those existing in the literature, a particular measurement procedure was selected for further development. The measurement is based on creating a spherical temperature field in a drill hole using a point source heater of constant heat flux. The bivariate temperature distribution 0 (r, t) is measured at several points along the length of the drillhole, radius r from the heater and at particular time intervals (t). A number of different evaluation methods were tested for calculating the unknown thermal conductivity (k) and diffusivity [] from the measured temperature and the known heat flux. The results showed that evaluation using the finite difference scheme and small temperature differences measured at points close together, cannot give a reasonable result. In order to solve the problem a new general analytical evaluation method is developed. Using an appropriate technique, it is possible to simultaneously obtain values for k and [], incorporating a semi least square technique to reduce the uncertainty in the evaluation. The new device and evaluation method makes it possible to obtain from a single drill hole highly precise k and [] values within an 8 hour period. The method has been used in several underground mines in the U.S. with good results.